Implementasi Media Sosial Facebook dan Instagram Sebagai Sarana Efektiv Hubungan Masyarakat di Madrasah Ibtidaiyah (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
This study aims to analyze the effectiveness of Facebook and Instagram as public relations communication tools at MI Darun Najah Srobyong, Jepara. A qualitative approach was employed using observation, in-depth interviews with the public relations team, teachers, parents, and community leaders, as well as documentation analysis. The findings indicate that both platforms have contributed to improving information transparency, community engagement, and the school's public image. However, several challenges were identified, including limited human resources and digital literacy gaps among parents. The study recommends content management training, digital literacy programs, and enhanced two-way interaction to optimize the role of social media in elementary school communication strategies.